Evidence From a Systematic Review and Meta-Analysis: Classical Impaired Glucose Tolerance Should Be Divided Into Subgroups of Isolated Impaired Glucose Tolerance and Impaired Glucose Tolerance Combined With Impaired Fasting Glucose, According to the Risk of Progression to Diabetes - Liu, Yupu; Li, Juan; Wu, Yuchao; Zhang, Han; Lv, Qingguo; Zhang, Yuwei; Zheng, Xiaofeng; Tong, Nanwei (Frontiers in Endocrinology, 2022)
Background: The American Diabetes Association (ADA) 2003 diagnostic criteria divide impaired glucose tolerance (IGT) into isolated impaired glucose tolerance with normal fasting glucose (I-IGT, IGT+NFG) and impaired glucose tolerance combined with impaired fasting glucose (IGT+IFG), while the World Health Organization (WHO) 1999 criteria do not. The aim of this meta-analysis was to evaluate whether IGT should be divided into I-IGT (IGT+NFG) or IGT+IFG according to their risk of progression to type 2 diabetes. Methods: The MEDLINE and EMBASE were searched to identify prospective cohort studies published in English prior to April 18, 2020. Review Manager 5.3 was used to calculate the pooled risk ratios (RRs) and 95% confidence intervals (CIs) as summary statistics for each included study. Results: Sixteen eligible studies (n =147,006) were included in the analysis. The subsequent incidence of type 2 diabetes was lower in the I-IGT (IGT+NFG) group than the IGT+IFG group (0.45 [95%CI 0.37, 0.55] according to WHO 1999 criteria and 0.59 [95%CI 0.54, 0.66] according to ADA 2003 criteria). It was higher in the I-IFG, I-IGT(IGT+NFG) and IGT+IFG groups than in the normoglycemic group (95%CI of 5.53 [3.78, 8.08], 5.21 [3.70, 7.34], and 11.87 [7.33, 19.20] according to the WHO 1999 criteria and 95%CI of 2.66 [2.00, 3.54], 3.34 [2.81, 3.97], and 6.10 [4.72, 7.88] according to the ADA 2003 criteria), In general, the incidence of diabetes in the IGT+IFG group was the highest in the prediabetic population. Conclusions: The present meta-analysis suggested that the established WHO diagnostic criteria for IGT should be revised to separately identify individuals with IGT+NFG or IGT+IFG.